2014
DOI: 10.1158/0008-5472.can-14-0209
|View full text |Cite
|
Sign up to set email alerts
|

GBV-C Infection and Risk of NHL among U.S. Adults

Abstract: Some retrospective studies suggest an association between infection with GB-virus C (GBV-C) and non-Hodgkin lymphoma (NHL). We evaluated this association prospectively in a nested case-control study within the U.S. Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO). Cases (N=658) and controls (N=1,316) were individually-matched by age, sex, race/ethnicity, timing of study entry and sample selection. Pre-diagnostic PLCO serum samples were tested for GBV-C RNA (as a measure of active infection)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
0
51
1
Order By: Relevance
“…The viral genome consists of a single open reading frame (ORF) of ∼3000 amino acids that encodes for multiple structural and non‐structural genes. Most investigations have failed to demonstrate any pathogenic consequence of HPgV replication on human disease reviewed in reference although it may be weakly associated with non‐Hodgkin lymphoma . HPgV is transmitted efficiently via intravenous and sexual routes, and the prevalence varies widely based on geographic location and the population studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The viral genome consists of a single open reading frame (ORF) of ∼3000 amino acids that encodes for multiple structural and non‐structural genes. Most investigations have failed to demonstrate any pathogenic consequence of HPgV replication on human disease reviewed in reference although it may be weakly associated with non‐Hodgkin lymphoma . HPgV is transmitted efficiently via intravenous and sexual routes, and the prevalence varies widely based on geographic location and the population studied.…”
Section: Introductionmentioning
confidence: 99%
“…There was no conclusive evidence for an association between survival and HPgV infection early in HIV disease; however, there was a significant reduction in mortality when HPgV infection was present later in HIV disease. Clearance of HPgV viremia is associated with accelerated HIV disease compared to non‐clearance …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that HPgV is not hepatotropic, but rather lymphotropic . In several studies, the correlation of HPgV infection with lymphoma has been reported . To note, HPgV infection is a risk factor of lymphoma, especially non‐Hodgkin's lymphoma, as demonstrated in a large‐scale study …”
Section: Introductionmentioning
confidence: 86%
“…Following its discovery, multiple studies evaluated the possible association of HPgV infection with a variety of clinical diseases. While a weak association between HPgV infection and non‐Hodgkin's lymphoma has been reported recently, all other studies found no causal link between HPgV infection and any clinical disease . In contrast, several studies reported that HPgV infection is associated with delayed HIV disease progression .…”
Section: Introductionmentioning
confidence: 91%